Optimal inverses and abstract splines - Corach, Gustavo (2016)
We extend the notion of optimal inverse introduced by S.K. Mitra for matrices, to operators in Hilbert spaces. We obtain necessary and sufficient conditions for the existence of these inverses for a closed range operator and apply these results to characterize the solutions of abstract smoothing spline problems.